2011
DOI: 10.1016/j.electacta.2011.01.073
|View full text |Cite
|
Sign up to set email alerts
|

On-demand photochemical stabilization of doping in light-emitting electrochemical cells

Abstract: A highly functional p-n junction doping structure can be realized within a light-emitting electrochemical cell under applied voltage via ion redistribution and electrochemical doping. This doping structure will however dissipate when the formation voltage is removed due to the mobility of the dopant counter-ions. A number of concepts aimed at a spatial immobilization of the ions and the related stabilization of the doping structure have been presented, but they all suffer from long and poorly controlled stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Optimal devices are achieved after stressing for 30 min at 30–100 V, depending on the channel length. In some cases, these ions can be chemically fixed via cross‐linking induced by annealing or UV‐light exposure in order to effectively lock them into their non‐equilibrium position …”
mentioning
confidence: 99%
“…Optimal devices are achieved after stressing for 30 min at 30–100 V, depending on the channel length. In some cases, these ions can be chemically fixed via cross‐linking induced by annealing or UV‐light exposure in order to effectively lock them into their non‐equilibrium position …”
mentioning
confidence: 99%
“…Gao and coworkers were first to demonstrate ionstabilization in a ''frozen-junction'' mode, when they performed the ion redistribution at room temperature and thereafter cooled down the device to a temperature at which the ions were effectively immobile [85,86]. Leger and co-workers developed this concept into a ''chemical-stabilization'' mode, when they and subsequently others attempted to stabilize a desired ion profile through chemical means, by endowing the ionic solvent, the ions, or a combination thereof with crosslinkable units that can be activated by heat, polarons, or light [87,88,90,93,94]. Although these ion-stabilization methods indeed are conceptually interesting, they have not yet matured into a practically useful device with maintained fast turn-on following extended storage in the idle state.…”
Section: Performance: Achieving Fast Turn-on High Efficiency and Lomentioning
confidence: 98%
“…A more novel approach to a fast turn-on constitutes a device tuning process, where the ions first are redistributed to allow for EDL formation and doping and then are stabilized in space, so that a subsequent turn-on only relies on a fast electronic process [85][86][87][88][89][90][91][92]. Gao and coworkers were first to demonstrate ionstabilization in a ''frozen-junction'' mode, when they performed the ion redistribution at room temperature and thereafter cooled down the device to a temperature at which the ions were effectively immobile [85,86].…”
Section: Performance: Achieving Fast Turn-on High Efficiency and Lomentioning
confidence: 99%
“…It has been demonstrated that after the initial electrochemical charging, the ions can be polymerized at the desired position within the LEC, thus preventing the reversibility of the device (22,75,76). Similarly, the ion conductor can be cured after the p-n junction is initially formed, eliminating the ion conductance in the LEC (26).…”
Section: Lecs With Fixed Junctionsmentioning
confidence: 99%